Penerapan Media Film Dalam Meningkatkan Keterampilan Menulis Teks Ulasan - Samrilla, Isra; Haliq, Abdul; Hapidah, Hapidah (TITIK DUA: Jurnal Pembelajaran Bahasa dan Sastra Indonesia, 2025)
This study aims to describe the improvement of review text writing skills by using movie media of X SMA 21 Makassar students. The type of research used in this study is the Classroom Action Research method. The research subjects amounted to 36 students. The research instruments used included observation, interviews, and tests. The results showed an increase in each cycle. The percentage of completeness of learning outcomes in writing review texts in the pre-cycle value of 46% increased to 56% in cycle I. Meanwhile, in cycle II, the completeness of learning outcomes in writing review texts in the pre-cycle value was 46%. While in cycle II, the completeness of learning outcomes increased to 84%. This shows that the application of movie media improves review text writing skills in class X.10 SMA Negeri 21 Makassar students.